Pengaruh Kekurangan Energi Kronis Pada Ibu Hamil Terhadap Berat Bayi Baru Lahir - Puspasari Hartono, Berlian; Suparji, Suparji; Nuryani, Nuryani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
High infant mortality rates (IMR) and low birth weight babies (LBW) are determined by the nutritional status of pregnant women. Pregnant women are a group that is vulnerable to nutritional problems. The purpose of this study was to determine the effect of chronic energy deficiency on pregnant women with newborns at the Manguharjo Health Center. This research is cross sectional analytic research. The population of all pregnant women who gave birth at the Manguharjo Health Center in 2022 was 439 people. Samples were taken using the Proportionate simple random sampling technique of 211 pregnant women. The independent variable is chronic energy deficiency in pregnant women while the dependent variable is newborn weight. Analysis with Chi Square test with significance α = 0.05. The results showed that out of 211 pregnant women, 17 pregnant women (8.1%) experienced chronic energy deficiency and 25 pregnant women (11.8%) gave birth to LBW babies. From the results of the Chi Square test, it was concluded that there was an effect of chronic energy deficiency on pregnant women with newborn weight at the Manguharjo Health Center, Madiun City, with a low level of association.